Recycling networks. Grassroots resilience tackling climate, environmental and poverty challenges: - Oloko, Michael (JOOUST, 2020)
The project aims at examining the challenges that innovative grassroots networks encounter and the livelihood practices they generate, to improve recycling and household waste collection in informal settlements of global South cities.
Keywords: Recycling; Climate; Environment; Poverty; Waste Collection